Symbiosis - Stone, Nic (Stone, Nic. Black Panther novel., 2022)
The royal palace of Wakanda is one of, if not the most secure facilities on this planet--or any other. So the anxiety Shuri feels when she's jolted out of sleep by the queen mother with the news that someone attempted to break into the palace--and succeeded--is significant. And as quickly as they broke in, they vanished. The search for this interloper, a mysterious "symbiote" with superhuman speed and strength, will lead Shuri to the Jabari Lands, a remote, unforgiving part of the country she has never seen. And what she discovers will be more shocking than she could have imagined.